Exogenous 2,4-Epibrassinolide Treatment Maintains the Quality of Carambola Fruit Associated With Enhanced Antioxidant Capacity and Alternative Respiratory Metabolism - Zhu, Xiaoyang; Chen, Yuxin; Li, Junyi; Ding, Xiaochun; Xiao, Shuangling; Fan, Silin; Song, Zunyang; Chen, Weixin; Li, Xueping (Frontiers in Plant Science, 2021)
Brassinosteroids act by delaying fruit ripening. The effects of different concentration of 2,4-epibrassinolide (eBL) treatments on carambola fruit ripening were investigated. The results show that treatment of 2.8 mg L-1, eBL with 10 min effectively delays ripening and maintains the quality of carambola fruit. This is achieved by retarding color changes and firmness losses while maintaining high level of soluble protein content and vitamin C, and low organic acid content. eBL-delayed senescence may be due to the inhibition of respiration rate and enhanced antioxidant system. It is noteworthy that eBL treatment markedly reduces the content of fructose-6-phosphate (6-P-F) and enhances total activity of cytochrome oxidase (CCO), glucose-6-phosphate dehydrogenase (G-6-PDH), and 6-phosphate gluconate dehydrogenase (6-PGDH). eBL treatment induces the IAA and GA contents but reduces that of ABA. In general, senescence retardation and quality improvement by eBL treatment may be due to the enhanced antioxidant capacity and altered respiratory pathways.